Prospecting Miocene Carbonate Hardground As Caprock, Case Study in Oyo Formation, Gunungkidul, Daerah Istimewa Yogyakarta - Ramadhan, Ichsan (Departemen Teknik Geologi, 2019)
Oyo Formation is located in Gading, Playen, Gunungkidul Regency, Province of Daerah Istimewa Yogyakarta. It has stratigraphic record that representative for study about carbonate hardground as caprocks in petroleum system because the hardground is well expose. This research is focused on study of carbonate hardground role as caprocks in petroleum system based on the characteristic of pore type, cement type and strength. The objective of the research is to identify Miocene carbonate hardground ability to be a caprock. The methods used in this research are measuring section to integrate stratigraphic record to reconstruct the sedimentation and diagenetic model in the depositional environment, petrography to reconstruct diagenesis model, and point load compressive strength test to assesses the maximum force of hardground can take as a caprock before it breaks. Result shows there are many hardground beds formed intercalated with limestones. Hardground is recrystallized and the pore and permeability are reduced due to aragonitic cementation in low energy environment. Result shows the maximum pressure hardground can hold is 2,737 MPa (UCS) and if situated as hydraulic seal, it will break in the depth greater than 279,514 meters. In conclusion, Miocene carbonate hardground with case study in Oyo Formation is not capable to be a good caprock in petroleum system.